Syrian Arab Republic : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that over the past three years, Syria has recovered from a half decade of weak growth, notwithstanding an unsettled regional environment and a sharp drop in oil production. The economic recovery has gained momentum, benefiting from inflows from Iraqi refugees and abundant liquidity in the Gulf region. Private investment has strengthened owing to an improved business climate, and exports have made strong gains, particularly in some Arab markets. The near-term outlook for growth and inflation is favorable.